Knitted fibrous filter media - Mullins, B.; King, Andrew; Mead-Hunter, Ryan; Heikamp, W. (2017)
© 2017 Elsevier Ltd. All rights reserved. Knitted fibrous filter media represent a special class of filter media, which tend to be utilized for industrial applications, usually related to mist separation in process industries. These filters are advantageous for many applications, as their knitted structure imparts significant mechanical strength-similar to woven filters, without the high packing density of most woven filters. In this chapter, we discuss advantages and disadvantages of knitted fibrous filter media in comparison to felted (nonwoven) and woven media. An overview of industrial applications is presented, plus a summary of studies related to pressure drop and efficiency and research specific to knitted mist eliminator media. Suggestions for further research are also provided.